Chemically strengthened glass

By setting a compressive stress layer and tensile stress layer in the chemically strengthened glass, and adjusting the strengthening filling rate and stress curve, the burst problem of glass during fracture in the prior art is solved, achieving high-strength and low-burst effects.

CN119317609APending Publication Date: 2025-01-14NIPPON ELECTRIC GLASS CO LTD

Patent Information

Application Number
CN202380048255.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-13
Filing Date
2023-06-29
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

Existing chemically reinforced glasses tend to show burst behavior when they break, and it is difficult to simultaneously inhibit burst and improve strength.

Method used

The surface part of the chemically strengthened glass is provided with a compressive stress layer, and a tensile stress layer is provided inside. By adjusting the strengthening filling rate FIOX to 0.75 or more and 1.00 or less, the tensile flat area, fracture toughness value and compression stress layer are optimized. Depth to control the curve of the stress curve to ensure that the glass is not prone to burst when it breaks.

Benefits of technology

It is achieved to increase the strength of chemically strengthened glass while suppressing bursting behavior during fracture, ensuring that the glass is not prone to rupture rupture when it is damaged, and to enhance its bending and drop strength.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119317609A_ABST
    Figure CN119317609A_ABST
Patent Text Reader

Abstract

Provided is a chemically strengthened glass which is provided with a compressive stress layer having compressive stress in a surface layer portion and with a tensile stress layer having tensile stress in the interior, and which has a strengthening filling rate FIOX represented by formula (1) of 0.75-1.00 (inclusive). UCT is the tensile square area of the chemically strengthened glass [MPa2. M], UCT limit is the burst threshold value of the chemically strengthened glass [MPa2. M], t is the thickness [m] of the chemically strengthened glass, DOC is the depth [m] of the compressive stress layer of the chemically strengthened glass, x is the depth [m] from the surface of the chemically strengthened glass, sigma (x) is the compressive stress value [MPa] at the depth x of the chemically strengthened glass, and sigma (x) is the compressive stress value [MPa] at the depth x of the chemically strengthened glass. K1C: fracture toughness value [MPa.m1 / 2] [mathematical formula 1] # imgabs0 # in thickness center part of chemically strengthened glass
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to chemically strengthened glass. Background Art

[0002] Chemically strengthened glass is widely used as cover glass for various electronic terminals, display devices, etc. Chemically strengthened glass has a compressive stress layer formed by ion exchange treatment on the surface, thereby suppressing the formation and growth of surface cracks and obtaining high strength (for example, Patent Document 1).

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: International Publication No. 2013 / 088856 Summary of the invention

[0006] Problems to be solved by the invention

[0007] As the strength of chemically strengthened glass increases, it tends to show explosive behavior such as breaking and shattering when it breaks. Therefore, the following attempts have been made in the past: based on the tensile stress value of the tensile stress layer, the chemically strengthened glass is evaluated in advance whether it has explosive behavior when it breaks. However, it is difficult to accurately evaluate in advance whether the chemically strengthened glass has explosive behavior when it breaks by the tensile stress value. As a result, the previous chemically strengthened glass has the following problem: it is impossible to simultaneously suppress the explosive behavior when breaking and improve the strength.

[0008] An object of the present invention is to provide a chemically strengthened glass capable of achieving high strength while suppressing bursting behavior during fracture.

[0009] Means for solving problems

[0010] (1) The chemically strengthened glass of the present invention, which has been created to solve the above-mentioned problems, is characterized in that it has a compressive stress layer having compressive stress in the surface layer portion, and a tensile stress layer having tensile stress in the interior portion, and a strengthening filling factor F represented by formula (A) is IOX It is 0.75 or more and 1.00 or less.

[0011] [Mathematical formula 1]

[0012]

[0013] [Mathematical formula 2]

[0014]

[0015] [Mathematical formula 3]

[0016]

[0017] U CT : The tensile square area of ​​chemically strengthened glass expressed by formula (B) [MPa 2 ·m]

[0018] U CT limit : The bursting threshold of chemically strengthened glass expressed by formula (C) [MPa 2 ·m]

[0019] t: Thickness of chemically strengthened glass [m]

[0020] DOC: Depth of compressive stress layer of chemically strengthened glass [m]

[0021] x: Depth from the surface of chemically strengthened glass [m]

[0022] σ(x): compressive stress value at depth x of chemically strengthened glass [MPa]

[0023] K 1C : Fracture toughness value of the composition at the center of the thickness of chemically strengthened glass [MPa·m 1 / 2 ]

[0024] The inventors of the present application have conducted intensive research and have found that the reinforcing filling rate F represented by the formula (A) IOX , it is possible to accurately evaluate in advance whether the chemically strengthened glass has bursting behavior when it breaks. Specifically, the following insight is obtained, that is, at the strengthening filling rate F IOX When the chemically strengthened glass is greater than 1, it is easy to produce bursting behavior when it is broken. IOX When the filling factor F is 1 or less, the chemically strengthened glass is less likely to explode when broken. IOX When the ratio is 1 or less, the bursting behavior of the chemically strengthened glass when broken can be suppressed almost reliably.

[0025] On the other hand, when strengthening the filling rate F IOX When the value is less than 0.75, the bursting behavior of the chemically strengthened glass when broken can be suppressed, but the chemical strengthening is insufficient and it is difficult to achieve high strength. Therefore, from the perspective of achieving high strength, it is necessary to increase the strengthening filling rate F to 0.75 as in the above-mentioned configuration. IOX Set to 0.75 or more.

[0026] (2) In the configuration of (1) above, it is preferred that the stretched square area U CT 0.90MPa 2 ·m or more.

[0027] (3) In the configuration of (1) or (2) above, it is preferred that the fracture toughness value K 1C 0.80MPa·m 1 / 2 above.

[0028] (4) In any one of the above-mentioned structures (1) to (3), preferably, the depth DOC of the compressive stress layer is 90 μm or more, and the tensile stress value CT at the depth t / 2 is 80 MPa or more.

[0029] (5) In any of the above (1) to (4), preferably, the thickness t is 0.1 to 1.5 mm, the compressive stress value CS at the surface is 700 MPa or more, and the compressive stress value CS at a depth of 30 μm is 30 The compressive stress value CS at a depth of 50 μm is above 140 MPa. 50 It is above 100MPa.

[0030] (6) In any one of the above-mentioned structures (1) to (5), the diffusion depth DOLK of potassium ions is preferably 4 μm or more.

[0031] (7) In any one of the above (1) to (6), a stress curve obtained by measuring the stress in the depth direction from the surface, assuming that the compressive stress is a positive number and the tensile stress is a negative number, may have a curved portion.

[0032] (8) In any of the above (1) to (7), the chemically strengthened glass may contain, as a glass composition, in mol %, 40% to 80% of SiO2, 10% to 30% of Al2O3, 0% to 10% of B2O3, 0.1% to 25% of Na2O, 0% to 10% of K2O, 0.1% to 20% of Li2O, 0% to 10% of MgO, and 0% to 10% of P2O5.

[0033] (9) In the configuration of (8) above, the chemically strengthened glass preferably contains, in terms of mol%, 50% to 70% of SiO2, 10% to 20% of Al2O3, 0% to 3% of B2O3, 1% to 25% of Na2O, 0% to 10% of K2O, 3% to 12% of Li2O, 0% to 5% of MgO, and 1% to 10% of P2O5 as a glass composition.

[0034] (10) In any of the above (1) to (7), the chemically strengthened glass may contain, in terms of mol%, 40% to 80% of SiO2, 10% to 30% of Al2O3, 0% to 3% of B2O3, 5% to 25% of Na2O, 0% to 5.5% of K2O, 0% to 0.09% of Li2O, and 0% to 10% of MgO.

[0035] (11) In any one of the above-mentioned structures (1) to (7), the chemically strengthened glass may be crystallized glass.

[0036] (12) In another embodiment of the chemically strengthened glass of the present invention, a compressive stress layer having compressive stress is provided on the surface layer portion, a tensile stress layer having tensile stress is provided inside, and a strengthening filling factor F represented by formula (D) is IOX It is 0.75 or more and 1.00 or less.

[0037] [Formula 4]

[0038]

[0039] [Mathematical formula 5]

[0040]

[0041] [Mathematical formula 6]

[0042]

[0043] U CT : The tensile square area of ​​chemically strengthened glass expressed by formula (E) [MPa 2 ·m]

[0044] U CT limit : The bursting threshold of chemically strengthened glass expressed by formula (F) [MPa 2 ·m]

[0045] t: Thickness of chemically strengthened glass [m]

[0046] DOC: Depth of compressive stress layer of chemically strengthened glass [m]

[0047] x: Depth from the surface of chemically strengthened glass [m]

[0048] σ(x): compressive stress value at depth x of chemically strengthened glass [MPa]

[0049] K 1C : Fracture toughness value of chemically strengthened glass before chemical strengthening [MPa·m 1 / 2 ]

[0050] Effects of the Invention

[0051] According to the present invention, it is possible to provide chemically strengthened glass that can achieve high strength while suppressing bursting behavior during fracture. BRIEF DESCRIPTION OF THE DRAWINGS

[0052] Figure 1 This is a schematic cross-sectional view showing a chemically strengthened glass according to an embodiment of the present invention.

[0053] Figure 2 This is a schematic diagram showing an example of a stress curve of a chemically strengthened glass according to an embodiment of the present invention.

[0054] Figure 3 This is a schematic diagram showing another example of a stress curve of the chemically strengthened glass according to the embodiment of the present invention.

[0055] Figure 4 This is a flowchart showing a method for producing chemically strengthened glass according to an embodiment of the present invention.

[0056] Figure 5 This is a flowchart showing a method for producing chemically strengthened glass according to an embodiment of the present invention.

[0057] Figure 6 It is the number of fragments and the square area of ​​stretching when chemically strengthened glass breaks. CT Graph of the relationship.

[0058] Figure 7 This is a diagram for explaining the pen drop test.

[0059] Figure 8 is the bursting threshold U of chemically strengthened glass CT limit and fracture toughness value K 1C Graph of the relationship.

[0060] Fig. 9 This is a diagram for explaining the damaging process when measuring the damaged four-point bending strength.

[0061] Fig.10 This is a diagram for explaining the bending fracture process when measuring the damaged four-point bending strength. DETAILED DESCRIPTION

[0062] Hereinafter, embodiments of the present invention will be described with reference to the drawings.

[0063] <Chemically strengthened glass>

[0064] like Figure 1 As shown, the chemically strengthened glass 1 of this embodiment is a plate-shaped or sheet-shaped glass chemically strengthened by ion exchange treatment. The thickness t of the chemically strengthened glass 1 is not particularly limited, and is, for example, 0.01 to 1.5 mm (preferably 0.1 to 1.0 mm).

[0065] The chemically strengthened glass 1 includes a compressive stress layer 2 and a tensile stress layer 3. The compressive stress layer 2 is formed on the surface layer including the main surface 1a and the end surface 1b of the chemically strengthened glass 1. The tensile stress layer 3 is formed inside the chemically strengthened glass 1, that is, formed at a position deeper than the compressive stress layer 2. Here, the so-called main surface 1a refers to the surface and back surface of the entire glass surface except the end surface 1b.

[0066] The strengthening filling rate F of the chemically strengthened glass 1 expressed by formula (1) is IOX It is 0.75 or more and 1.00 or less. Strengthening filling rate F IOX Preferably, it is 0.76 or more and less than 1.00, 0.80 or more and 0.99 or less, or 0.85 or more and 0.98 or less. In this way, a chemically strengthened glass 1 can be obtained that can achieve high strength while suppressing explosive behavior such as shattering or crushing during fracture.

[0067] [Mathematical formula 7]

[0068]

[0069] [Mathematical formula 8]

[0070]

[0071] [Mathematical formula 9]

[0072]

[0073] U CT : Square tensile area of ​​chemically strengthened glass [MPa 2 ·m]

[0074] U CT limit :The bursting threshold of chemically strengthened glass [MPa 2 ·m]

[0075] t: Thickness of chemically strengthened glass [m]

[0076] DOC: Depth of compressive stress layer of chemically strengthened glass [m]

[0077] x: Depth from the surface of chemically strengthened glass [m]

[0078] σ(x): compressive stress value at depth x of chemically strengthened glass [MPa]

[0079] K 1C : Fracture toughness value of chemically strengthened glass before chemical strengthening [MPa·m 1 / 2 ]

[0080] The tensile square area U of chemically strengthened glass 1 CT Preferably 0.90 MPa 2 m or more, 0.95MPa 2 m or more, 1.00MPa 2 m or more, 1.05MPa 2 m or more. If so, the mechanical strength such as bending strength of the chemically strengthened glass 1 is improved.

[0081] Fracture toughness value K of chemically strengthened glass 1 1C Preferably 0.80 MPa·m 1 / 2 Above, 0.81MPa·m 1 / 2 Above, 0.82MPa·m 1 / 2 Above, 0.83MPa·m 1 / 2 By setting it in this way, the mechanical strength, such as bending strength, of the chemically strengthened glass 1 is improved.

[0082] The compressive stress layer depth DOC of the chemically strengthened glass 1 is preferably 90 μm or more, 100 μm or more, 105 μm or more, 110 μm or more, or 115 μm or more. In this way, the chemically strengthened glass 1 is less likely to break even if scratches are formed on the surface.

[0083] The diffusion depth DOLK of K ions in the chemically strengthened glass 1 is preferably 4 μm or more, 4.5 μm or more, 5 μm or more, or 6 μm or more. In this way, the chemically strengthened glass 1 is less likely to break even if scratches are formed on the surface.

[0084] The tensile stress value CT at the depth t / 2 (center of the plate thickness) of the chemically strengthened glass 1 is preferably 80 MPa or more, 85 MPa or more, 90 MPa or more, or 95 MPa or more. If so, it is easy to increase the surface compressive stress and tend to obtain high strength. On the other hand, if CT is excessively increased, the chemically strengthened glass 1 tends to show bursting behavior when broken. Therefore, CT is preferably 125 MPa or less, 120 MPa or less, 115 MPa or less, or 110 MPa or less. However, whether the chemically strengthened glass 1 has bursting behavior when broken cannot be accurately evaluated by the CT value, so the above-mentioned F needs to be considered. IOX The value of .

[0085] The compressive stress value CS at the surface of the chemically strengthened glass 1 is preferably 700 MPa or more, 750 MPa or more, 800 MPa or more, or 850 MPa or more. The compressive stress value CS at a depth of 30 μm of the chemically strengthened glass 1 is 30 Preferably, it is 140 MPa or more, 150 MPa or more, 160 MPa or more, or 170 MPa or more. The compressive stress value CS of the chemically strengthened glass 1 at a depth of 50 μm 50 Preferably, it is 100 MPa or more, 105 MPa or more, 110 MPa or more, or 115 MPa or more. If so, the mechanical strength such as bending strength and drop strength of the chemically strengthened glass 1 is improved.

[0086] Here, CS, DOC, DOLK, CT, U CTFor example, it can be derived based on the value measured using a surface stress meter (e.g., FSM-6000LE manufactured by Orihara Seisakusho), or a value obtained by synthesizing the values measured using a surface stress meter and a scattered light photoelastic stress meter (e.g., SLP-1000 manufactured by Orihara Seisakusho). K 1C is the value measured by the indentation method (Indentation Fracture method; IF method) in accordance with JIS R1607, and is the average value measured 10 times.

[0087] Fracture toughness value K 1C For example, it can be measured by the indentation method (IF method) in accordance with JIS R1607. It should be noted that the fracture toughness value K 1C can also be measured using other known methods. For example, the fracture toughness value K 1C can also be measured using the SEPB method.

[0088] In addition, the fracture toughness value K 1C can also be obtained by calculation based on the mirror constant (original Japanese: ミラー定数). In order to measure the fracture toughness value K of the central part composition 1C , the glass sample of this composition is processed into a specified size, and the measurement test of the above method is carried out. In the case where it is difficult to process the strengthened glass with high strength into a specified size, the calculation based on the mirror constant can also be used as an alternative method. It is known that there is a certain correlation between the fracture toughness of glass and glass ceramics and their mirror constants (Mecholsky et al., J. Mater. Sci., 11, 1310-1319 (1976)). In the present invention, the fracture toughness value K 1C can be obtained from the relational expression of the following formula (4) based on the mirror constant A m . It should be noted that the mirror constant A m can be obtained by observing the mirror radius of the cross section after breaking a glass sample of any size under a specified bending stress.

[0089] A m = 3.4141K 1C + 1.228……(4)

[0090] K 1C : Fracture toughness value (MPa / m 1 / 2 )

[0091] A m : Mirror constant (MPa·m 1 / 2 )

[0092] The damaged four-point bending strength of the chemically strengthened glass 1 is preferably 190 MPa or more, 200 MPa or more, 210 MPa or more, or 220 MPa or more. In this way, the chemically strengthened glass 1 can be suitably used for foldable devices that are used by being bent.

[0093] An example of a stress curve of the chemically strengthened glass 1 obtained by measuring the stress in the depth direction from the surface is shown in FIG. Figure 2 It should be noted that, in this specification, unless otherwise specified, the magnitude of each stress is expressed as an absolute value.

[0094] like Figure 2 As shown in FIG. 1 , in order to achieve a large CS and a deep DOC, the stress curve of the chemically strengthened glass 1 has a greatly curved portion X. That is, the stress curve of the chemically strengthened glass 1 is divided into a plurality of portions with different slopes when a straight line approximation is performed. If so, the drop strength of the chemically strengthened glass 1 is greatly improved. Therefore, when the chemically strengthened glass is used for the cover glass of a smartphone, etc., the probability of breakage when dropped can be greatly reduced.

[0095] In the stress curve of the chemically strengthened glass 1, the compressive stress reaches the maximum (CS) at the surface, and the stress gradually decreases as the depth relative to the surface increases, and the stress becomes zero at the depth corresponding to the DOC. That is, the DOC is synonymous with the depth of the compressive stress layer 2. In the region deeper than the DOC, the tensile stress layer 3 having tensile stress extends.

[0096] The stress curve of the chemically strengthened glass 1 is not limited to Figure 2 For example, it is also possible to Figure 3 As shown, it is a stress curve having a first peak P1, a first valley B1, a second peak P2, and a second valley B2 in order from the surface side. The first peak P1 is formed on the surface of the chemically strengthened glass 1. The second valley B2 is formed at the center of the thickness of the chemically strengthened glass 1 (t / 2). The first valley B1 and the second peak P2 are formed in the range from the surface to the DOC. In the case of such a stress curve, a plurality of curved portions X are formed.

[0097] The chemically strengthened glass 1 is preferably, for example, aluminosilicate glass.

[0098] As an example of aluminosilicate glass, for chemically strengthened glass 1, as the central composition of the glass, it can contain, in mol%, 40% to 80% SiO2, 10% to 30% Al2O3, 0% to 10% B2O3, 0.1% to 25% Na2O, 0% to 10% K2O, 0.1% to 20% Li2O, 0% to 10% MgO, and 0% to 10% P2O5.

[0099] It should be noted that the central composition of the chemically strengthened glass 1 in the present invention refers to the glass composition of the central portion of the thickness of the chemically strengthened glass 1. The central composition of the chemically strengthened glass 1 is the same as the glass composition of the chemically strengthened glass before chemical strengthening. In addition, the fracture toughness value of the central composition of the chemically strengthened glass of the present invention refers to the fracture toughness value of the glass sample in the unstrengthened state having the central composition, and is the same as the fracture toughness value of the chemically strengthened glass before chemical strengthening.

[0100] For the chemically strengthened glass 1, more specifically, as a core composition, it can contain, in mol%, 50% to 70% SiO2, 10% to 20% Al2O3, 0% to 3% B2O3, 1% to 25% Na2O, 0% to 10% K2O, 3% to 12% Li2O, 0% to 5% MgO, and 1% to 10% P2O5.

[0101] SiO2 is a component of the network that forms glass. If the content of SiO2 is too little, it is difficult to vitrify, and in addition, the thermal expansion coefficient becomes too high, and thermal shock resistance is easily reduced. Thus, the suitable lower limit range of SiO2 is calculated as more than 40%, more than 50%, more than 55%, more than 57%, more than 59%, and particularly more than 61% in mole %. On the other hand, if the content of SiO2 is too much, then the meltability and formability are easily reduced, and the thermal expansion coefficient becomes too low in addition, and it is difficult to match the thermal expansion coefficient of the surrounding materials. Thus, the suitable upper limit range of SiO2 is calculated as less than 80%, less than 70%, less than 68%, less than 66%, less than 65%, and less than 64.5% in mole %.

[0102] Al2O3 is the composition that improves ion exchange performance, and is the composition that improves strain point, Young's modulus, fracture toughness, Vickers hardness in addition.Therefore, Al2O3 suitable lower limit range is calculated by mole % as more than 10%, more than 12%, more than 13%, more than 14%, more than 14.4%, more than 15%, more than 15.3%, more than 15.6%, more than 16%, more than 16.5%, more than 17%, more than 17.2%, more than 17.5%, more than 17.8%, more than 18%, greater than 18%, more than 18.3%, more than 18.5%, more than 18.6%, more than 18.7%, more than 18.8%.On the other hand, if Al2O3 content is too much, then high temperature viscosity rises, and fusibility, formability are easily reduced.In addition, easily separate out devitrified crystal in glass, be difficult to utilize overflow down-draw method etc. to be formed into plate-like. Particularly using alumina-based refractory as a formed body refractory, utilizing overflow downdrawing method to be formed into a plate-like state, it is easy to separate out the devitrified crystal of spinel at the interface with alumina-based refractory. In addition acid resistance also reduces, and is difficult to be applied to acid treatment process. Therefore, Al2O3 suitable upper limit range is counted in mol% as below 30%, below 25%, below 21%, below 20.5%, below 20%, below 19.9%, below 19.5%, below 19.0%, below 18.9%.

[0103] B2O3 is a component that reduces high temperature viscosity and density, stabilizes glass, makes crystals difficult to precipitate, and reduces liquidus temperature. If the content of B2O3 is too little, the stress depth during the ion exchange of Li ions contained in the glass with Na ions in the molten salt is too deep, and as a result, the compressive stress value of the compressive stress layer tends to become smaller. In addition, the glass becomes unstable and the resistance to devitrification may be reduced. Therefore, the suitable lower limit range of B2O3 is 0% or more, 0.1% or more, 0.2% or more, 0.5% or more, 0.6% or more, 0.7% or more, 0.8% or more, 0.9% or more, and 1% or more in mole %. On the other hand, if the content of B2O3 is too much, the stress depth may become shallow. In particular, the efficiency of the ion exchange of Na ions contained in the glass with K ions in the molten salt is easily reduced, and the depth of the compressive stress layer tends to become smaller. Therefore, the appropriate upper limit range of B2O3 is, in terms of mol %, less than 10%, less than 5%, less than 4%, less than 3.8%, less than 3.5%, less than 3.3%, less than 3.2%, less than 3.1%, less than 3%, and less than 2.9%.

[0104] Na2O is an ion exchange component, and is also a component that reduces high temperature viscosity and improves meltability and formability. In addition, Na2O is a component that improves devitrification resistance, and is particularly a component that suppresses devitrification caused by reaction with alumina-based refractory. Therefore, the appropriate lower limit range of Na2O is 0.1% or more, 1% or more, 3% or more, 4% or more, 5% or more, 6% or more, 7% or more, 7.5% or more, 8% or more, 8.5% or more, 8.8% or more, and 9% or more in terms of mole %. On the other hand, if the content of Na2O is too much, the thermal expansion coefficient is too high, and the thermal shock resistance is easily reduced. In addition, the component balance of the glass composition collapses, and there is a situation where the devitrification resistance is reduced. Therefore, the appropriate upper limit range of Na2O is 25% or less, 21% or less, 20% or less, 19% or less, 18% or less, 15% or less, 13% or less, 11% or less, and 10% or less in terms of mole %.

[0105] K2O is a component that reduces high temperature viscosity and improves solubility and formability. However, if the content of K2O is too much, the thermal expansion coefficient is too high and the heat shock resistance is easily reduced. In addition, the compressive stress value of the outermost surface is easily reduced. Therefore, the appropriate upper limit range of K2O is calculated as mol% below 10%, below 7%, below 6%, below 5%, below 4%, below 3%, below 2%, below 1.5%, below 1%, less than 1%, less than 0.5%, less than 0.1%. It should be noted that if the viewpoint of deepening the stress depth is emphasized, the appropriate lower limit range of K2O is calculated as mol% above 0%, above 0.1%, above 0.3%, and above 0.5%.

[0106] Li2O is an ion exchange component, particularly for ion exchange of Li ions contained in glass with Na ions in molten salt, and obtaining a component of deep stress depth. In addition, Li2O is a component that reduces high temperature viscosity and improves solubility and formability, and is also a component that improves Young's modulus. Therefore, the suitable lower limit range of Li2O is calculated by mole % as more than 0.1%, more than 3%, more than 4%, more than 5%, more than 5.5%, more than 6.5%, more than 7%, more than 7.3%, more than 7.5%, more than 7.8%, more than 8%. The suitable upper limit range of Li2O is calculated by mole % as less than 20%, less than 15%, less than 13%, less than 12%, less than 11.5%, less than 11%, less than 10.5%, less than 10%, less than 9.9%, less than 9%, less than 8.9%.

[0107] MgO is a component that reduces high temperature viscosity and improves meltability, formability, strain point, and Vickers hardness. Among alkaline earth metal oxides, it is a component that has a great effect on improving ion exchange performance. However, if the content of MgO is too much, the devitrification resistance is easily reduced, and it is particularly difficult to suppress the devitrification caused by the reaction with alumina-based refractory materials. Therefore, the appropriate content of MgO is 0 to 10%, 0 to 5%, 0.1 to 4%, 0.2 to 3.5%, 0.5 to less than 3% in mole %.

[0108] P2O5 is a component that improves ion exchange performance, especially a component that deepens stress depth. In addition, it is also a component that improves acid resistance. If the content of P2O5 is too little, it may not be possible to fully exert the ion exchange performance. In particular, the efficiency of ion exchange between Na ions contained in the glass and K ions in the molten salt is easily reduced, and the depth of the compressive stress layer is easily reduced. In addition, the glass becomes unstable and the resistance to devitrification may be reduced. Therefore, the appropriate lower limit range of P2O5 is calculated in mole % as 0% or more, 0.1% or more, 0.4% or more, 0.7% or more, 1% or more, 1.2% or more, 1.4% or more, 1.6% or more, 2% or more, 2.3% or more, 2.5% or more, and 3% or more. On the other hand, if the content of P2O5 is too much, the glass will undergo phase separation or water resistance will be easily reduced. In addition, the stress depth during ion exchange between Li ions contained in the glass and Na ions in the molten salt is too deep, as a result, the compressive stress value of the compressive stress layer is easily reduced. Therefore, the appropriate upper limit range of P2O5 is 10% or less, 5% or less, 4.5% or less, or 4% or less in terms of mol%.

[0109] As an example of other aluminosilicate glass, for chemically strengthened glass 1, as a core composition, in terms of mol%, 40% to 80% of SiO2, 10% to 30% of Al2O3, 0% to 3% of B2O3, 5% to 25% of Na2O, 0% to 5.5% of K2O, 0% to 0.09% of Li2O, and 0% to 10% of MgO may be contained. That is, chemically strengthened glass 1 may not substantially contain Li2O. However, in order to achieve a large CS and a deep DOC in chemically strengthened glass 1, it is preferred that chemically strengthened glass 1 contains Li2O.

[0110] The chemically strengthened glass 1 may be a crystallized glass. Crystallized glass is a glass obtained by subjecting amorphous glass to a heat treatment (crystallization treatment) to precipitate inorganic crystals, and contains inorganic crystals in the glass. Here, the so-called amorphous glass refers to glass in which no diffraction peak indicating crystals is observed by powder X-ray diffraction.

[0111] As an example of crystallized glass formed of aluminosilicate glass, for chemically strengthened glass 1, as the central composition, by mass %, it can contain 58% to 70% SiO2, 15% to 30% Al2O3, 2% to 10% Li2O, 0% to 10% Na2O, 0% to 10% K2O, 0% to 15% Na2O+K2O, 0% to 15% MgO+CaO+SrO+BaO+ZnO, 0.1% to 6% SnO2, 0.5% to 6% ZrO2, 0% to 4% TiO2, 0% to 6% P2O5, and the degree of crystallization can be 1 to 95%. The degree of crystallization can be evaluated using an X-ray diffraction device (Smart Lab, a fully automatic multi-purpose horizontal X-ray diffraction device manufactured by Rigaku).

[0112] Since the chemically strengthened glass 1 is a chemically strengthened glass having the above-mentioned core composition, the chemically strengthened glass before chemical strengthening preferably has a glass composition exemplified as the core composition of the chemically strengthened glass 1 described above.

[0113] <Method for producing chemically strengthened glass>

[0114] like Figure 4 As shown, the method for producing a chemically strengthened glass according to the present embodiment includes a preparation step S1 and a chemical strengthening step S2.

[0115] In the preparation step S1, chemically strengthened glass is prepared. The chemically strengthened glass is glass having substantially the same shape, size and glass composition as the chemically strengthened glass 1 described above. The chemically strengthened glass refers to glass before ion exchange treatment, and the chemically strengthened glass refers to glass after ion exchange treatment.

[0116] Chemically strengthened glass can be obtained by, for example, cutting and processing a plate-shaped or sheet-shaped mother glass obtained by a forming method such as an overflow down-draw method, a slit down-draw method, a float method, or a redraw method into small pieces of glass. In order to obtain a smooth surface, an overflow down-draw method is preferably used as a forming method. It should be noted that when forming by an overflow down-draw method, the chemically strengthened glass has a forming confluence surface inside.

[0117] In the chemical strengthening step S2, the chemically strengthened glass is chemically strengthened by ion exchange treatment to obtain a chemically strengthened glass 1 having a compressive stress layer 2 and a tensile stress layer 3. The number of ion exchange treatments is not particularly limited and may be only once or multiple times. When multiple ion exchange treatments are performed, the number of ion exchange treatments is preferably 2 times.

[0118] When the chemically strengthened glass contains Na ions and Li ions in the glass and undergoes multiple ion exchange treatments, it is preferred that after the first ion exchange treatment of immersing the chemically strengthened glass in a molten salt containing a NaNO3 molten salt, a second ion exchange treatment of immersing the chemically strengthened glass in a molten salt containing a KNO3 molten salt is performed. If so, a large CS and a deep DOC can be easily achieved.

[0119] In particular, it is preferred that in the first ion exchange treatment, the chemically strengthened glass is immersed in a NaNO3 molten salt or a mixed molten salt of NaNO3 and KNO3, and in the second ion exchange treatment, the chemically strengthened glass is immersed in a mixed molten salt of KNO3 and LiNO3. If so, a structure showing the following characteristics can be obtained: Figure 2 Chemically strengthened glass 1 having a stress curve at a curved portion X is shown.

[0120] In the first ion exchange process, the Li ions contained in the glass are ion exchanged with the Na ions in the molten salt. In the case of using a mixed molten salt of NaNO3 and KNO3, further, the Na ions contained in the glass are ion exchanged with the K ions in the molten salt. Here, the ion exchange of the Li ions contained in the glass with the Na ions in the molten salt is faster than the ion exchange rate of the Na ions contained in the glass with the K ions in the molten salt, and the efficiency of the ion exchange is high. In the second ion exchange process, the Na ions near the surface of the glass (from the surface to the shallow area of ​​20% of the thickness t) are ion exchanged with the Li ions in the molten salt, and the Na ions near the surface of the glass (from the shallow area of ​​20% of the thickness of the plate) are ion exchanged with the K ions in the molten salt. That is, in the second ion exchange process, it is possible to introduce K ions with a large ionic radius while detaching the Na ions near the surface of the glass. As a result, it is possible to increase the compressive stress value of the outermost surface while maintaining a deep stress depth.

[0121] In the first ion exchange step, the treatment temperature (temperature of the molten salt) is preferably 360 to 400° C., and the treatment time (ion exchange time) is preferably 30 minutes to 6 hours. In the second ion exchange step, the treatment temperature is preferably 370 to 400° C., and the treatment time is preferably 15 minutes to 3 hours.

[0122] With regard to forming a stress curve having a curved portion X, in the mixed molten salt of NaNO3 and KNO3 used in the first ion exchange process, the concentration of NaNO3 is preferably higher than the concentration of KNO3, and in the mixed molten salt of KNO3 and LiNO3 used in the second ion exchange process, the concentration of KNO3 is preferably higher than the concentration of LiNO3.

[0123] In the mixed molten salt of NaNO3 and KNO3 used in the first ion exchange step, the concentration of KNO3 is preferably 0 mass %, 0.5 mass %, 1 mass %, 5 mass %, 7 mass %, 10 mass %, 15 mass %, 20 to 90 mass %. If the concentration of KNO3 is too high, the compressive stress value formed when the Li ions contained in the glass are ion-exchanged with the Na ions in the molten salt may be excessively reduced. In addition, if the concentration of KNO3 is too low, the stress measurement using a surface stress gauge may become difficult.

[0124] In the mixed molten salt of KNO3 and LiNO3 used in the second ion exchange step, the concentration of LiNO3 is preferably greater than 0 to 5 mass%, greater than 0 to 3 mass%, greater than 0 to 2 mass, and 0.1 to 1 mass%. If the concentration of LiNO3 is too low, it is difficult for Na ions near the surface of the glass to be separated. On the other hand, if the concentration of LiNO3 is too high, the compressive stress value formed by the ion exchange of Na ions near the surface of the glass with K ions in the molten salt may be excessively reduced.

[0125] When the chemically strengthened glass contains Na ions in the glass and only one ion exchange treatment is performed, it is preferred to immerse the chemically strengthened glass in an ion exchange treatment in a molten salt containing a KNO 3 molten salt. In this case, the Na ions contained in the glass are ion exchanged with the K ions in the molten salt.

[0126] When the chemically strengthened glass contains Li ions in the glass and only one ion exchange treatment is performed, it is preferred to immerse the chemically strengthened glass in an ion exchange treatment in a molten salt containing a NaNO 3 molten salt. In this case, the Li ions contained in the glass are ion exchanged with the Na ions in the molten salt.

[0127] The conditions of the chemical strengthening step S2 are preferably such that the strengthening filling factor F of the chemically strengthened glass 1 is IOX The ratio is appropriately adjusted to be 0.75 or more and 1.00 or less. For example, the type, concentration, treatment temperature, treatment time, etc. of the molten salt in the ion exchange treatment are adjusted.

[0128] When the chemically strengthened glass 1 is a crystallized glass, Figure 5 As shown, the method for manufacturing chemically strengthened glass further includes a heating treatment (crystallization) step S3 after the preparation step S1 as described above and before the chemical strengthening step S2. In the heating treatment step S3, for example, the chemically strengthened glass as an amorphous glass is heat-treated at 700 to 840° C. for 0.1 to 15 hours. As a result, at least one selected from β-eucryptite solid solution, β-spodumene solid solution and zirconium dioxide is precipitated in the glass as a precipitated crystal.

[0129] Example

[0130] Hereinafter, the glass article of the present invention will be described based on Examples. It should be noted that the following Examples are merely illustrative, and the present invention is not limited to the following Examples at all.

[0131] <Production of chemically strengthened glass>

[0132] Chemically strengthened glasses having the glass compositions shown in Table 1 were prepared.

[0133] [Table 1]

[0134]

[0135] Specifically, the glass raw materials described in Table 1 are prepared and melted in a test melting furnace. Thereafter, the obtained molten glass is formed into a plate or sheet, and cut into a specified size to obtain a chemically strengthened glass. For the chemically strengthened glass of composition D, after further heating treatment at 780°C for 3 hours, it is heated at 830°C for 1 hour to prepare a crystallized glass. It should be noted that the thickness of the chemically strengthened glass of compositions A to C is set to 0.7 mm, and the thickness of the chemically strengthened glass of composition D is set to 0.6 mm. In addition, for the chemically strengthened glass sample obtained as described above, the fracture toughness value K is measured. 1C The fracture toughness value K obtained 1C It refers to the fracture toughness value of the composition at the center of the thickness of the chemically strengthened glass after chemical strengthening described below.

[0136] <Derivation of formula (1)>

[0137] The chemically strengthened glass (measurement sample) was prepared by subjecting the above-mentioned glass for chemical strengthening to ion exchange treatment by changing the type of molten salt, treatment time (immersion time), and treatment temperature.

[0138] Specifically, all chemically strengthened glasses were subjected to only one ion exchange treatment. For chemically strengthened glasses of compositions A to B, ion exchange was performed by immersing them in a KNO3 molten salt. For chemically strengthened glasses of composition C, ion exchange was performed by immersing them in a NaNO3 molten salt. For chemically strengthened glasses (crystallized glass) of composition D, ion exchange was performed by immersing them in a mixed molten salt of KNO3 and LiNO3.

[0139] The treatment time (immersion time in molten salt) of the chemically strengthened glass of composition A is adjusted between 4 and 96 hours. The treatment time of the chemically strengthened glass of composition B is adjusted between 2 and 64 hours. The treatment time of the chemically strengthened glass of composition C is adjusted between 6 and 10 hours. The treatment time of the chemically strengthened glass of composition D is set to 90 hours or 120 hours.

[0140] The treatment temperature (temperature of the molten salt) of the chemically strengthened glass of compositions A and B was 450° C. The treatment temperature of the chemically strengthened glass of composition C was 380° C. The treatment temperature of the chemically strengthened glass of composition D was 430° C.

[0141] Then, the number of fragments and the tensile square area U of each chemically strengthened glass produced as described above were examined when it was broken by a pen drop test. CT The results are shown in Figure 6 middle. Figure 6 In the figure, the horizontal axis represents U CT , the vertical axis represents the number of fragments at the time of fracture.

[0142] like Figure 7 As shown, in the pen drop test, the tip of the diamond pen 6 is dropped and hits the main surface of the chemically strengthened glass 4, while the chemically strengthened glass 4 corresponding to the composition A to D is placed on the stone platform 5, so that the chemically strengthened glass 4 is broken. Thereafter, the number of fragments of the chemically strengthened glass 4 at this time is measured. The chemically strengthened glass 4 is set to a rectangle of 26 mm × 76 mm. The thickness of the chemically strengthened glass 4 is set to 0.7 mm (measurement sample corresponding to the composition A to C) or 0.6 mm (measurement sample corresponding to the composition D). The diamond pen 6 uses the model 579-50-62-1 (weight 10 g) of Tokyo Glass Machinery (TGK). The drop height H1 of the diamond pen 6 is set to 20 mm. It should be noted that as a method for measuring the number of fragments, in addition to using a method of visually counting the number of fragments of the chemically strengthened glass 4, a method of randomly measuring the area of ​​the fragments after the breakage and estimating the number of fragments can also be used.

[0143] Stretched square area U of chemically strengthened glass 4 CT It is obtained by formula (2). In this case, the stress curve of the chemically strengthened glass 4 can be derived based on the value obtained by using FSM-6000LE (manufactured by Orihara Seisakusho) or the value obtained by combining the values ​​obtained by using FSM-6000LE and SLP-2000 (manufactured by Orihara Seisakusho).

[0144] according to Figure 6 As a result, for chemically strengthened glass 4 of compositions A to D, the maximum stretched square area U for which the number of fragments must be less than 50 is read respectively. CT The value of the burst threshold U CT limit), study and fracture toughness value K 1C For the result, the fracture toughness value K is set on the horizontal axis. 1C , set the burst threshold U in the vertical axis CT limit And make a graph, and put the resulting graph in Figure 8 It should be noted that, when 50 or more fragments are measured within 10 seconds immediately after fracture, it is known from experience that there is a tendency for the fragments to exhibit explosive behavior of breaking and shattering at the time of fracture.

[0145] according to Figure 8 The results also show that at the fracture toughness value K 1C With the burst threshold U CT limit Moreover, if the points in the figure are approximated by a straight line, we can get y=1.618x-0.121[MPa 2 ·m], that is, as shown in formula (3), we can get U CT limit =1.618K 1C -0.121[MPa 2 ·m] Therefore, if the stretched square area U of the chemically strengthened glass is CT 1.618K 1C -0.121 represents U CT limit Below, the chemically strengthened glass is less likely to show bursting behavior when broken. That is, as shown in formula (1), U CT / U CT limit The defined reinforcement filling rate F IOX A value of 1 or less can be an index for accurately evaluating whether or not the chemically strengthened glass exhibits bursting behavior when broken.

[0146] Here, the fracture toughness value K of each chemically strengthened glass is 1C The burst threshold U calculated according to formula (3) CT limit The relationship is shown in Table 2.

[0147] [Table 2]

[0148]

[0149] <Evaluation of properties of chemically strengthened glass using formula (1)>

[0150] The chemically strengthened glasses (compositions B, C, and D) were chemically strengthened under the conditions shown in Table 3 to produce chemically strengthened glasses, and various properties were evaluated. Samples Nos. 1 to 2 and 4 to 8 are examples of the present invention, and Sample No. 3 is a comparative example.

[0151] [Table 3]

[0152]

[0153] For samples No. 1 to 4, only the first ion exchange step was performed for a total of one ion exchange treatment, and for samples No. 5 to 8, the first ion exchange step and the second ion exchange step were performed for a total of two ion exchange treatments. It should be noted that "Na100" in the table means ion exchange treatment by immersion in a molten salt having a concentration of 100% by mass of NaNO3, "Na95 / Li5" means ion exchange treatment by immersion in a molten salt having a concentration of 95% by mass of NaNO3 and a concentration of 5% by mass of KNO3, and "K100" means ion exchange treatment by immersion in a molten salt having a concentration of 100% by mass of KNO3.

[0154] K 1C It is a value measured by the indentation method (IF method) in accordance with JIS R1607 and is the average value of 10 measurements. 1C This is a value measured for each glass sample before ion exchange.

[0155] CS, DOLK, DOC, CT, CS 30 , CS 50 The value is calculated based on a stress curve obtained from the values ​​measured by FSM-6000LE or a stress curve obtained by synthesizing the values ​​measured by FSM-6000LE and SLP-2000.

[0156] U CT limit Using K determined as described above 1C And the formula (3) is used for determination.

[0157] U CT The stress curve measured as described above and the formula (2) are used for measurement.

[0158] F IOX Using the U determined as described above CT limit , U CT And the formula (1) is used for determination.

[0159] The damaged four-point bending strength is measured by performing a damage process of forming shallow scratches on the surface of the chemically strengthened glass and then performing a bending fracture process of applying bending stress to the chemically strengthened glass to fracture it. Fig. 9The test device (damage device) 7 shown in the figure is used for the test. The test device 7 is equipped with a steel hammer 8 weighing 550g. The hammer 8 has a rod-shaped arm 9 and a head 10. One end (upper end) of the arm 9 is supported by a support shaft 11, and the arm 9 is made to be able to rotate around the support shaft 11. The head 10 is provided on the side surface of the other end (lower end) of the arm 9. The head 10 has a collision surface 10a that collides with the main surface 13a of the chemically strengthened glass 13 through the sandpaper 12. The chemically strengthened glass 13 is supported on a SUS-made platform 14 in a manner that the main surface is along the vertical direction. Sandpaper (No. 180) 12 is fixed to one main surface 13a of the chemically strengthened glass 13.

[0160] In the damaging step, after the head 10 of the arm 9 is arranged at a predetermined drop height H2 (100 mm), the arm 9 is rotated toward the chemically strengthened glass 13 by the action of gravity, so that the collision surface 10a of the head 10 collides with the sandpaper 12 and the chemically strengthened glass 13. As a result, a scratch shallower than the depth of the compressive stress layer is formed on the main surface 13a of the chemically strengthened glass 13.

[0161] like Fig.10 As shown, in the bending fracture step, a four-point bending tester 15 is used. The four-point bending tester 15 includes a pressurizing jig 16 for pressing the chemically strengthened glass 13 and a supporting jig 17 for supporting the chemically strengthened glass 13 .

[0162] In the bending fracture process, the bending stress applied to fracture the chemically strengthened glass 13 is measured by a four-point bending tester 15. The four-point bending test uses a method in accordance with JIS-R1601. Regarding the specific conditions of the four-point bending test, the width W1 of the press jig 16 is set to 20 mm, the width W2 of the support jig 17 is set to 40 mm, and the descending speed of the press jig 16 is set to 3 mm / min. It should be noted that the chemically strengthened glass 13 is arranged in such a manner that the main surface 13a formed with a scar in the damage process is in contact with the support jig 17.

[0163] Regarding the bursting behavior, the pen drop test mentioned above (see Figure 7 ) When chemically strengthened glass is broken, if 50 or more fragments are measured within 10 seconds just after the break, it is set as "yes", and if less than 50 fragments are measured within 10 seconds just after the break, it is set as "no".

[0164] According to the results in Table 3, it can also be confirmed that in F IOX In the samples No. 1 to 2 and 4 to 8 where F is less than 1, the chemically strengthened glass does not show bursting behavior when broken. IOXIn sample No. 3 where F is greater than 1, the chemically strengthened glass exhibits bursting behavior when broken. In addition, although samples No. 5 to 8 were subjected to multiple ion exchange treatments, in terms of evaluating the bursting behavior of such chemically strengthened glass when broken, F IOX is effective.

[0165] If we compare F IOX Sample No. 7 and Sample No. 8 show similar values, and it can be confirmed that K 1C 0.8MPa·m 1 / 2 The above samples No.7 and K 1C Less than 0.8MPa·m 1 / 2 Compared with sample No. 8, the damaged four-point bending strength becomes stronger.

[0166] In samples No. 5 to 7, which were subjected to the ion exchange treatment twice, CS was 700 MPa or more, CS 30 140MPa or more, CS 50 The results are as follows: the stress curves of samples No. 5 to 8 are as follows: Figure 2 The bend X is shown.

[0167] Industrial Applicability

[0168] The chemically strengthened glass of the present invention can be used for, for example, smartphones, mobile phones, tablet computers, personal computers, digital cameras, touch panel displays, cover glasses of other display devices, vehicle-mounted display devices, vehicle-mounted panels, and the like.

[0169] Description of Reference Numerals

[0170] 1 Chemically strengthened glass

[0171] 1a Main surface

[0172] 1b End face

[0173] 2 Compressive stress layer

[0174] 3 Tensile stress layer

[0175] 4 Chemically strengthened glass (measurement sample)

[0176] 5 Stone Platform

[0177] 6 Diamond Pen

[0178] 7 Test equipment

[0179] 8 Hammer

[0180] 9 Arm

[0181] 10 Head

[0182] 11 Support shaft

[0183] 12 Sandpaper

[0184] 13 Chemically strengthened glass (measurement sample)

[0185] 14 Platform

[0186] 15 Testing machine

[0187] 16 Pressurized fixture

[0188] 17 Support fixture

Claims

1. A chemically strengthened glass, characterized in that: A compressive stress layer having compressive stress is provided on the surface layer, and a tensile stress layer having tensile stress is provided inside. The reinforcement filling rate F expressed by formula (A) IOX is greater than or equal to 0.75 and less than or equal to 1.00, U CT : The tensile square area of ​​chemically strengthened glass expressed by formula (B), in MPa 2 m, U CT limit : The bursting threshold of chemically strengthened glass expressed by formula (C), in MPa 2 m, t: thickness of chemically strengthened glass, in meters, DOC: Depth of the compressive stress layer of chemically strengthened glass, in meters. x: Depth from the surface of chemically strengthened glass, in meters, σ(x): compressive stress value at depth x of chemically strengthened glass, in MPa, K 1C : Fracture toughness value of the composition at the center of the thickness of chemically strengthened glass, unit: MPa·m 1 / 2 .

2. The chemically strengthened glass according to claim 1, wherein: Stretched square area U CT 0.90MPa 2 ·m or more.

3. The chemically strengthened glass according to claim 1 or 2, wherein: Fracture toughness value K 1C 0.80MPa·m 1 / 2 above.

4. The chemically strengthened glass according to claim 1 or 2, wherein: The depth DOC of the compressive stress layer is 90 μm or more. The tensile stress value CT at the depth t / 2 is 80 MPa or more.

5. The chemically strengthened glass according to claim 1 or 2, wherein: Thickness t is 0.1mm~1.5mm, The compressive stress value CS at the surface is above 700MPa. Compressive stress value CS at a depth of 30μm 30 140MPa or more, Compressive stress value CS at a depth of 50μm 50 It is above 100MPa.

6. The chemically strengthened glass according to claim 1 or 2, wherein: The diffusion depth DOLK of potassium ions is 4 μm or more.

7. The chemically strengthened glass according to claim 1 or 2, wherein: A stress curve obtained by measuring stress in a depth direction from the surface, assuming that compressive stress is a positive number and tensile stress is a negative number, has a curved portion.

8. The chemically strengthened glass according to claim 1 or 2, wherein: The glass composition at the center of the thickness contains, in mol%, 40% to 80% SiO2, 10% to 30% Al2O3, 0% to 10% B2O3, 0.1% to 25% Na2O, 0% to 10% K2O, 0.1% to 20% Li2O, 0% to 10% MgO, and 0% to 10% P2O5.

9. The chemically strengthened glass according to claim 8, wherein: The glass composition of the thickness center portion contains, in mol %, 50% to 70% SiO2, 10% to 20% Al2O3, 0% to 3% B2O3, 1% to 25% Na2O, 0% to 10% K2O, 3% to 12% Li2O, 0% to 5% MgO, and 1% to 10% P2O5.

10. The chemically strengthened glass according to claim 1 or 2, wherein: The glass composition of the thickness center portion contains, in mol %, 40% to 80% SiO2, 10% to 30% Al2O3, 0% to 3% B2O3, 5% to 25% Na2O, 0% to 5.5% K2O, 0% to 0.09% Li2O, and 0% to 10% MgO. The chemically strengthened glass according to claim 1 or 2, which is crystallized glass.

Citation Information

Patent Citations

  • Display cover glass and display cover glass fabrication method

    WO2013088856A1

Cited By

  • High-strength chemically strengthened glass and preparation method thereof

    CN120817726A